The technology of biological wastewater treatment of the Antarctic station Akademician Vernadsky - L.A. Sabliy; E.V. Kuzminskiy; V.S. Zhukova; M.V. Blyashina (Ukrainian Antarctic Journal, 2014)
The Antarctic station Akademician Vernadsky is in the area of ​​low temperatures (about 0 °C in summer, winter –18 °C) refers to small objects and wastewater characterized by low flow of domestic wastewater, the uneven nature of their admission to the sewer pipes and uneven quality and quantitative composition of pollutants. A new efficient technology biological treatment of wastewater with immobilized microorganisms. Found that the most effective carrier for immobilization of microorganisms is textured nylon fiber "VIYA". With the use of immobilized biomass concentration reached      30 g/dm3, which allows to increase the destructive power of bioreactors to reduce their size, to achieve a high degree of wastewater treatment.